Sports Injury Management Education for Parents of Students of Putra Balung Jaya Football School - Afaf Syahab; Ahmad Sulaiman; Ahmad Bahriyanto; Novy Eurika; Ramadhan Wahyu; Ahmad Mico Andreansyah (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
Sports injuries are a major obstacle for the development of youth football players. Limited knowledge of parents in initial injury management can worsen the athlete’s condition and delay recovery. This community service program aimed to enhance the knowledge and skills of parents, coaches, and young players of the Putra Balung Jaya Football School in Jember regarding sports injury management. The activities consisted of three phases: preparation, implementation, and evaluation, using lectures, interactive discussions, demonstrations, and hands-on practice of the RICE (Rest, Ice, Compression, Elevation) technique. Evaluation results showed a significant improvement in participants’ knowledge and skills, with an average post-test score increasing by 38% compared to the pre-test, and 75% of participants successfully performing injury management techniques. This program is expected to be implemented sustainably as a preventive and promotive measure in youth football development.